Cenografia e subjetivação em discursos literários de posicionamento espiritual, produzidos por Frei Antonio das Chagas, no Barroco português - Celestino, Ricardo (2019)
This research aims to examine the scenography and subjectification processes in spiritual positioning through literary speeches, produced by Friar Antonio das Chagas, in Portuguese Baroque and compiled in Cartas Espirituais. The corpus collected presents doctrinal purposes related to knowing how to live, based on biblical prudence. In order to legitimize their doctrinal functions, the enunciator makes a mise-en-scène an spirituality that harmonizes Christian humanism and mystical asceticism. Therefore, dialogues among Literature, Religion, Spirituality and Philosophy are made with other discursive marks of baroque esthetics. Our thesis problematizes the literary discourse of spiritual positioning, based on the French-inspiration discourse analysis, mainly on the studies of Maingueneau (2000, 2005, 2006b, 2007, 2008a, 2008b, 2011, 2015), since they allow us an enunciative-discursive approach of the constituted corpus. For the analysis, interdiscursive categories have been used in order to mobilize the discursive formations of baroque esthetics, enunciation scenes that allow the enunciative acts unfolding and processes of subjectivation, in regard to consolidate the ascetic-mystical spirituality and Christian humanist. Finally, the paratopy, as a condition of literary speech, is observed as a model of life and moral conduct based on spirituality. The results obtained from the analysis indicate that the literary speeches of spiritual positioning written by Friar Antonio das Chagas propose models of life for a social, ethical and moral world. The combination of the discursive formations in the functioning of the speeches occurs through the unfolding produced by the enunciator between what has been instituted by the social environment and what has been captured during the enunciation. Hence, the construction of a paratopic speech implies a domain that is only possible in the enunciative-discursive practice, which sediments a certain way of dealing with the Absolute / God and extracting from this relation, a moral trajectory for social practices